2015
DOI: 10.1098/rspb.2015.1946
|View full text |Cite
|
Sign up to set email alerts
|

Why does offspring size affect performance? Integrating metabolic scaling with life-history theory

Abstract: Within species, larger offspring typically outperform smaller offspring. While the relationship between offspring size and performance is ubiquitous, the cause of this relationship remains elusive. By linking metabolic and life-history theory, we provide a general explanation for why larger offspring perform better than smaller offspring. Using high-throughput respirometry arrays, we link metabolic rate to offspring size in two species of marine bryozoan. We found that metabolism scales allometrically with off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 66 publications
4
73
0
Order By: Relevance
“…Bugula neritina Linnaeus, 1758, is a bryozoan common to sessile marine communities worldwide and is used extensively as a model for studies on life‐history strategies (Wendt ; Allen & Marshall ; Pettersen et al . ; Cameron et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Bugula neritina Linnaeus, 1758, is a bryozoan common to sessile marine communities worldwide and is used extensively as a model for studies on life‐history strategies (Wendt ; Allen & Marshall ; Pettersen et al . ; Cameron et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Once embryogenesis is complete, the developed non-feeding larvae are released into the plankton where they are competent to settle almost immediately, yet remain dependent on maternally derived energy reserves from release as larvae through post-settlement until the end of metamorphosis. This 'dependent phase' (sensu [23]) lasts approximately 2 days before the development of the first zooid with feeding structure (lophophore) is complete, and offspring feed for themselves.…”
Section: Materials and Methods (A) Study Species Site And Larval Massmentioning
confidence: 99%
“…The released larvae were then immediately photographed on a glass slide using a Moticam 5 digital camera (Motic, Hong Kong, China) mounted on a dissecting microscope as per standard techniques developed previously [24]. Measurements of larval body area and length of the ciliated groove were estimated to the nearest micrometres using IMAGEJ software (v. 1.47) and larvae mass estimates based on calculations obtained in a previous study [23]. Once photographed, larvae were then pipetted in a drop of seawater directly onto roughened acetate sheets to induce settlement.…”
Section: Materials and Methods (A) Study Species Site And Larval Massmentioning
confidence: 99%
“…Burgess et al () found that when the dispersal period of a bryozoan with a similar life history, Bugula neritina , is extended, there is selection for larger offspring size. Burgess's findings have intuitive appeal for three reasons: dispersal is costly for nonfeeding offspring (Strathmann , Bennett and Marshall ), larger offspring are released with more energy, and larger offspring use proportionally less energy during dispersal than smaller offspring (Pettersen et al ). These three criteria also apply to our study species, Watersipora , but we found the reverse pattern to Burgess: colonies that were larger as offspring perform initially worse when they experience an extended dispersal period.…”
Section: Discussionmentioning
confidence: 99%